2011
DOI: 10.1111/j.1600-0625.2011.01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke-induced early growth response-1 regulates the expression of the cysteine-rich 61 in human skin dermal fibroblasts

Abstract: Tobacco smoke is known to be an element contributing to accelerate premature skin ageing. Cysteine-rich 61 (Cyr61) is a member of the connective tissue factor CCN (Cyr61, CTGF and Nov) family, and early growth response-1 (Egr-1) is a generally expressed member of the zinc-finger family of transcription factors. To investigate the regulatory potential of Egr-1 on expression of Cyr61 by smoking, this study examined the hypothesis that cigarette smoke-induced Egr-1 induces expression of Cyr61 in human skin dermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
(44 reference statements)
1
11
0
Order By: Relevance
“…CYR61 is also overexpressed in RA synovial tissue and plays a critical role in the proliferation of rheumatoid arthritis synovial fibroblasts (30). CYR61 expression is induced in human skin dermal fibroblasts after exposure to cigarette smoke (31). In our study, four SNPs in CYR61 were associated with GO, with one, the promoter SNP rs3753793, even being associated with GD.…”
Section: Discussionsupporting
confidence: 48%
“…CYR61 is also overexpressed in RA synovial tissue and plays a critical role in the proliferation of rheumatoid arthritis synovial fibroblasts (30). CYR61 expression is induced in human skin dermal fibroblasts after exposure to cigarette smoke (31). In our study, four SNPs in CYR61 were associated with GO, with one, the promoter SNP rs3753793, even being associated with GD.…”
Section: Discussionsupporting
confidence: 48%
“…Clinically, the effect of zoledronate, a drug that represses bone metastasis of tumors, on CCN1 via FOXO 3a is worthy of note in relation to breast cancer chemotherapy (45). The induction of CCN1 in skin fibroblasts by cigarette smoke through Egr1 also suggests a possible role in CCN1 in skin aging due to smoking (46). Other classical CCN2 inducers include angiotensin II and endothelin, the latter of which mediates, in part, the TGF-β-induced enhancement of CCN2 gene expression (3,21,47).…”
Section: Ccn Regulators and Their Action Extracellular Ccn Regulatorsmentioning
confidence: 98%
“…It was later shown that skin fibroblasts from thyroid healthy individuals express both these genes in response to cigarette smoking [20]. We have recently demonstrated that several immediate early genes including CYR61, EGR1 and COX-2 are overexpressed in orbital tissue of smokers with severe GO as compared to nonsmokers [21].…”
Section: Discussionmentioning
confidence: 99%